Cosmic views of N. N. Moiseev and their place in Russian cosmism - Karako, Petr S. (Journal of the Belarusian State University. Sociology, 2019)
The article reveals the content of cosmic views of N. N. Moiseev, their place in the system of Russian cosmism. The features of the comprehension of the biosphere, its evolution into the noosphere and the expression of scientific knowledge in the relevant theoretical positions are revealed. Emphasizes the importance of the cosmist substantiation of the idea of coevolution of humankind and the biosphere, the role of environmental and moral imperatives in the implementation of this idea. Moreover the relevance of the provisions regarding the environmental education of pupils and students and the need for their implementation at the present time is proved.
Keywords: Russian cosmism; biosphere; noosphere; math modeling; co-evolution; environmental imperative; moral imperative; environmental education